A review of wireless power transfer using magnetoelectric structures. (1st November 2022) - Saha, Orpita; Truong, Binh Duc; Roundy, Shad
Abstract: Wireless power transfer (WPT) has received increasing attention primarily as a means of recharging batteries in the last few decades. More recently, magnetoelectric (ME) structures have been investigated as alternative receiving antennas in WPT systems. ME structures can be particularly useful for small scale devices since their optimal size is much smaller than traditional receiving coils for a given operating frequency. WPT systems using ME laminate receivers have been shown to be helpful in wirelessly powering various sensors and biomedical implants. In recent years, a large number of studies have been conducted to improve the performance of ME composites, in which various configurations have been proposed, along with the use of different magnetostrictive and piezoelectric materials. In addition, many efforts have been devoted to miniaturizing ME devices. An essential obstacle to overcome is to eliminate the need for a DC bias field that is commonly required for the operation of ME structures. In this review paper, we will discuss the basic principle of ME effects in composites, materials currently in use, various ME receiver structures, performance measures, limitations, challenges, and future perspectives for the field of WPT. Furthermore, we propose a power figure of merit which we use to compare recent ME WPT research papers.